Lithium battery diaphragm with low moisture content and high circulation rate and preparation method thereof
By using lithium slurry synergistically modified lithium slurry with polycrystalline mullite whiskers and barium sulfate in the lithium battery separator, the interlaced 3D mesh structure is formed, which solves the problem of shrinkage and high water content of lithium battery separator at high temperatures, and achieves more High heat resistance, mechanical strength and circulation magnification improve the safety performance and cost-effectiveness of the battery.
Patent Information
- Application Number
- CN202411551177.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-18
AI Technical Summary
The existing lithium battery separators are prone to shrink at high temperatures, resulting in battery short circuits and safety hazards. The high water content will affect the stability of the electrolyte and the cycling rate of the battery.
The lithium paste is used to synergically modify polycrystalline mullite whiskers and barium sulfate to form an interlaced 3D mesh structure to improve the heat resistance and mechanical strength of the membrane and reduce the water content.
It significantly improves the stability of lithium battery separators at high temperatures, reduces water content, enhances the circulation rate and safety performance of the battery, and reduces the cost of the battery.
Smart Images

Figure CN119481576A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery separators, and in particular relates to a low-moisture and high-cycle-rate lithium battery separator and a preparation method thereof. Background Art
[0002] As environmental problems become increasingly severe, more and more new energy projects have attracted social attention, among which electric vehicles are particularly popular. As the power source of electric vehicles, the safety and endurance of lithium-ion batteries are the focus of scientific research. As one of the key inner components of ion batteries, the performance of the diaphragm determines the interface structure and internal resistance of the battery, which directly affects the battery capacity, cycle and safety performance.
[0003] In ion batteries, the diaphragm absorbs electrolyte and allows the conduction of lithium ions while blocking the passage of electrons. It can also block the contact between the positive and negative electrodes to prevent short circuits. The thermal shrinkage performance of the diaphragm directly affects the safety of the battery. High water content in the diaphragm will cause the battery to bulge and reduce ion conductivity. Weak mechanical strength of the diaphragm will cause the diaphragm to be perforated and short-circuited when the battery is subjected to external stress.
[0004] Conventional lithium battery separators are PP / PE separators or separator coatings, which have average high heat resistance for batteries, high water content, and high short circuit rate.
[0005] For example, lithium batteries currently made with conventional coated diaphragms will cause the internal temperature of the battery to rise sharply when the external and internal circulation conditions are abnormal, such as charging and discharging, low temperatures in winter, and high temperatures in summer. The conventional coated diaphragms begin to shrink after 100°C (the shrinkage rate is 20-60%), and the battery short circuits and battery blistering will occur after shrinkage, posing serious safety hazards. This is mainly because the binder of the conventional coated diaphragm fails when the temperature rises, causing the mutual binding force between the ceramic particles, the binder, and the base film to disappear, resulting in battery short circuits and battery blistering.
[0006] In addition, the conventional alumina coated diaphragm has a high water content in the battery, and water will react with lithium hexafluorophosphate in the electrolyte to generate phosphorus oxyfluoride, lithium fluoride and hydrogen fluoride (H2O+LiPF6→POF3+LiF+2HF), and hydrogen fluoride is a strong acid that will react again with the alumina on the diaphragm (Al2O3+6HF=2AlF3+3H2O), thereby destroying the internal environment of the electrolyte and blocking the ion channel, increasing its internal resistance and reducing ion conductivity; the high water content of the diaphragm will also cause certain harm to the packaging of the lithium-ion battery. The HF generated by H2O and LiPF6 (lithium hexafluorophosphate) is a weak acid, but it is highly corrosive and can corrode the metal of the outer packaging. In severe cases, it will cause electrolyte leakage. Summary of the invention
[0007] In view of the deficiencies of the prior art, the object of the present invention is to provide a lithium battery separator with low moisture content and high cycle rate.
[0008] Another object of the present invention is to provide a method for preparing the above-mentioned low-moisture and high-cycle rate lithium battery separator.
[0009] The purpose of the present invention is achieved through the following technical solutions.
[0010] A low-moisture, high-cycle-rate lithium battery diaphragm comprises a base film and a coating on the base film, wherein the coating comprises polycrystalline mullite whiskers, barium sulfate and a binder, wherein the ratio of the polycrystalline mullite whiskers, barium sulfate and the binder is (10-20): (15-45): (3-8) by mass.
[0011] In the above technical solution, the adhesive is a polyacrylate adhesive.
[0012] In the above technical solution, the low-moisture and high-cycle-rate lithium battery separator also includes: a wetting agent and a dispersant. In terms of mass fraction, the ratio of barium sulfate, wetting agent and dispersant is (15-45): (0.05-1.0): (0.1-0.8).
[0013] In the above technical solution, the wetting agent is sodium isopropylnaphthalenesulfonate.
[0014] In the above technical solution, the dispersant is one or a mixture of sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate and polyvinyl alcohol (PVA).
[0015] In the above technical solution, the length of the polycrystalline mullite whisker is 10 to 100 nm.
[0016] The method for preparing the above-mentioned low-moisture and high-cycle-rate lithium battery separator comprises: coating a lithium battery slurry on a base film, drying, obtaining a coating on the base film, and obtaining a low-moisture and high-cycle-rate lithium battery separator.
[0017] In the above technical solution, the drying time is 1 to 3 minutes, and the drying temperature is 50 to 80°C.
[0018] In the above technical solution, the coating speed is 50 to 80 m / min.
[0019] In the above technical solution, the thickness of the coating is 2 to 5 μm.
[0020] A lithium battery slurry comprises: water, polycrystalline mullite whiskers, barium sulfate, a binder, a wetting agent and a dispersant. Calculated by mass, the ratio of the polycrystalline mullite whiskers, barium sulfate, the binder, the wetting agent and the dispersant is (10-20): (15-45): (3-8): (0.05-1.0): (0.1-0.8).
[0021] In the above technical solution, the ratio of water to polycrystalline mullite whiskers is (55-80):(10-20) by mass.
[0022] The method for preparing the lithium battery slurry comprises: mixing polycrystalline mullite whiskers, barium sulfate, water and a dispersant until they are uniform, then adding a binder and a wetting agent, and mixing them until they are uniform to obtain the lithium battery slurry.
[0023] In the above technical solution, polycrystalline mullite whiskers, barium sulfate, water and a dispersant are mixed and stirred at a rotation speed of 2500 to 3500 r / min and a revolution speed of 50 to 60 r / min for 30 to 40 minutes until they are uniform.
[0024] In the above technical solution, after adding the binder and the wetting agent, stirring is performed at a rotation speed of 2000 to 3000 r / min and a revolution speed of 30 to 40 r / min for 30 to 40 minutes until the mixture is uniform, thereby obtaining a lithium battery slurry.
[0025] Application of barium sulfate and polycrystalline mullite whiskers to synergistically reduce the water content of the separator.
[0026] Application of barium sulfate and polycrystalline mullite whiskers to synergistically improve the heat resistance of diaphragms.
[0027] Application of barium sulfate and polycrystalline mullite whiskers to synergistically improve battery cycle rate.
[0028] The battery market has put forward new requirements for battery separators. Battery separators need to develop in the direction of thinner thickness and better heat resistance, which further highlights the importance of thermal shrinkage of battery separators. In order to improve the heat resistance of battery separators, reduce safety problems such as short circuits caused by thermal shrinkage of battery separators, and improve battery reliability, the present invention uses a new material polycrystalline mullite whisker to make lithium battery slurry to modify the separator.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The diaphragm prepared from lithium battery slurry containing polycrystalline mullite whiskers is not easy to shrink at high temperature, can meet the requirements of battery winding assembly, and greatly improves the safety performance of the battery;
[0031] 2. An interlaced 3D network structure is generated between barium sulfate (particles) and polycrystalline mullite whiskers. Polycrystalline mullite whiskers can be interspersed between barium sulfate (particles). After the binder fails, the alumina particles can still be kept from falling off and the coating frame can be stable. Based on this network structure, it is easier to evaporate water when preparing the diaphragm, reducing the water content of the diaphragm. Barium sulfate (particles) and polycrystalline mullite whiskers jointly adjust the porosity and pore size distribution of the diaphragm, forming a channel for ion movement, allowing ions in the electrolyte to pass through, thereby achieving the purpose of blocking the current and ensuring the safety of battery use. Polycrystalline mullite whiskers improve the ionic conductivity of the diaphragm, increase the current density, and avoid local overheating caused by uneven current density;
[0032] 3. Barium sulfate and polycrystalline mullite whiskers are interlaced and support each other, so that there is a certain gap between barium sulfate (particles) and polycrystalline mullite whiskers, which better enables lithium ion conduction to block the passage of electrons and maintain good battery performance;
[0033] 4. Compared with other high-performance materials, polycrystalline mullite whiskers are relatively cheap, which can reduce the cost of batteries while ensuring battery performance;
[0034] 5. Polycrystalline mullite whiskers and barium sulfate will not react with hydrogen fluoride, thus greatly improving the cycle rate and charge and discharge times of the battery;
[0035] 6. When the lithium battery slurry containing polycrystalline mullite whiskers is coated on the base film, the polycrystalline mullite whiskers can play a reinforcing role, effectively disperse and bear the stress applied by the outside world, prevent the expansion of cracks, and thus improve the overall mechanical strength of the diaphragm.
[0036] Using polycrystalline mullite whiskers to modify the surface of the diaphragm can effectively improve the heat resistance of the battery diaphragm, make the diaphragm less likely to deform at high temperatures, and enhance the diaphragm's ability to withstand high temperatures. The polycrystalline mullite whiskers have a moderate diameter, excellent suspension and rheological properties, good leveling properties, and good heat resistance. Applying them to the diaphragm not only increases the diaphragm's heat resistance, but also improves the diaphragm's mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a SEM of the separator prepared from the slurry of Example 1. DETAILED DESCRIPTION
[0038] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0039] The raw material information involved in the following examples is as follows:
[0040] Polycrystalline mullite whiskers have a chemical composition of Al2O3 72-77wt%, SiO2 22-17wt%, B2O3 3-5wt%, and P2O5 1.5-3.0wt%. They are chemically stable, insoluble in hydrofluoric acid, and resistant to corrosion by organic solvents. They have a melting point of 1840°C. The length of the polycrystalline mullite whiskers is 10-100nm.
[0041] Mullite (granules): density 2.5-3.20g / cm 3 , Mohs hardness 6-7, melting temperature about 1910℃, high refractoriness, still very stable at 1800℃, decomposes into corundum and liquid phase at 1810℃, has good chemical corrosion resistance, and stable thermochemical properties.
[0042] The length of the aluminum oxide whiskers is 10 to 100 nm.
[0043] Alumina (particles): D50: 1.1 microns;
[0044] Barium sulfate (particles): D50: 1.0 μm;
[0045] Boehmite (particles): D50: 0.9 μm;
[0046] Mullite (particles): D50: 1.0 micron;
[0047] Polyacrylate adhesive, purchased from Shanghai Sanrui;
[0048] Sodium isopropylnaphthalenesulfonate was purchased from Shanghai Sanrui.
[0049] In the following embodiments, the base film is a PE film with a thickness of 9 microns.
[0050] In the following examples, water is ultrapure water.
[0051] Thermomechanical analysis (TMA): The instrument used is TA400 produced by Shanghai Jituo Technology. The diaphragm is made into a sample with a width of 3 mm and a length of 8 mm and placed in TA400. The tensile force is set to 0.03N and the heating rate is set to 5℃ / min to obtain the membrane rupture temperature (used to characterize the mechanical strength).
[0052] Ionic conductivity: The test temperature is 20-25°C, and the test relative humidity is 40%.
[0053] Examples 1 to 3
[0054] A method for preparing lithium battery slurry comprises: mixing polycrystalline mullite whiskers, barium sulfate (particles), water and a dispersant, stirring at a rotation speed of 2500 r / min and a revolution speed of 50 r / min for 30 min until uniform, then adding a binder and a wetting agent, stirring at a rotation speed of 2500 r / min and a revolution speed of 30 r / min for 30 min until uniform, to obtain lithium battery slurry, wherein the binder is a polyacrylate binder (polyacrylate is polymerized from methyl acrylate, ethyl acrylate and butyl acrylate), the wetting agent is sodium isopropylnaphthalene sulfonate, and the dispersant is polyvinyl alcohol (PVA), and the ratio of water, polycrystalline mullite whiskers, barium sulfate (particles), binder, wetting agent and dispersant is X in parts by mass. The value of X is shown in Table 1.
[0055] Table 1
[0056] Lithium battery slurry X Example 1 64:10:25:3:0.2:0.8 Example 2 64:15:20:3:0.2:0.8 Example 3 64:20:15:3:0.2:0.8
[0057] Comparative Example 1
[0058] A lithium battery slurry is basically the same as Example 1, except that "barium sulfate (particles)" is replaced by "mullite (particles)".
[0059] Comparative Example 2
[0060] A lithium battery slurry is basically the same as Example 1, except that "barium sulfate (particles)" is replaced by "aluminum oxide (particles)".
[0061] Comparative Example 3
[0062] A lithium battery slurry is basically the same as Example 1, except that "barium sulfate (particles)" is replaced by "boehmite (particles)".
[0063] Comparative Example 4
[0064] A lithium battery slurry is substantially the same as that of Example 1, except that the "polycrystalline mullite whiskers" are replaced by "alumina whiskers".
[0065] Comparative Example 5
[0066] A lithium battery slurry is basically the same as Example 1, except that "polycrystalline mullite whiskers" are replaced by "alumina whiskers" and "barium sulfate (particles)" are replaced by "mullite (particles)".
[0067] Comparative Example 6
[0068] A lithium battery slurry is basically the same as Example 1, except that "polycrystalline mullite whiskers" are replaced by "alumina whiskers" and "barium sulfate (particles)" are replaced by "alumina (particles)".
[0069] Comparative Example 7
[0070] A lithium battery slurry is substantially the same as Example 1, except that “polycrystalline mullite whiskers” are replaced by “alumina whiskers” and “barium sulfate (particles)” are replaced by “boehmite (particles)”.
[0071] Comparative Example 8
[0072] A lithium battery slurry is substantially the same as that of Example 1, except that "polycrystalline mullite whiskers" are replaced by "mullite (granular)".
[0073] Examples 4 to 6 and Comparative Examples 9 to 16
[0074] A battery, comprising: a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode comprises a positive electrode current collector (aluminum foil) and a positive electrode coating loaded on the positive electrode current collector (the positive electrode material in the positive electrode coating is lithium manganate), the negative electrode comprises a negative electrode current collector (copper foil) and a negative electrode coating loaded on the negative electrode current collector (the negative electrode material in the negative electrode coating is lithium titanate), the electrolyte is a mixture of an electrolyte and a solvent, the electrolyte is lithium hexafluorophosphate (LiPF6), and the solvent is ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) A mixture of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a ratio of 1:1:1 by mass, the concentration of the electrolyte in the electrolyte is 1 mol / L, and the method for preparing the diaphragm is: using a coating machine to coat the slurry on both sides of the base film, and pulling it into a drying device through a traction roller to dry it at 60°C for 0.8 minutes to obtain a diaphragm, wherein the coating speed is 80m / min, the single-sided coating thickness formed by the coating is 1.0μm, and the total double-sided coating thickness is 2.0μm. The slurry is one of the lithium battery slurries prepared in Examples 1 to 3 and Comparative Examples 1 to 8.
[0075] Table 2
[0076] Diaphragm Slurry for preparing diaphragm Example 4 Example 1 Example 5 Example 2 Example 6 Example 3 Comparative Example 9 Comparative Example 1 Comparative Example 10 Comparative Example 2 Comparative Example 11 Comparative Example 3 Comparative Example 12 Comparative Example 4 Comparative Example 13 Comparative Example 5 Comparative Example 14 Comparative Example 6 Comparative Example 15 Comparative Example 7 Comparative Example 16 Comparative Example 8
[0077] The diaphragms obtained in the above embodiments and comparative examples were tested, and the test results are shown in Table 3.
[0078] Table 3
[0079]
[0080] It can be seen from Table 3 that the shrinkage rate of the diaphragm prepared by the lithium battery slurry of Examples 1-3 is within 1%; the shrinkage rate of the diaphragm prepared by the lithium battery slurry of Comparative Examples 1-8 is above 26.5%. It can be clearly seen that the diaphragm prepared by the lithium battery slurry containing polycrystalline mullite whiskers and barium sulfate has better thermal shrinkage;
[0081] The water contents of the diaphragms prepared from the lithium battery slurries of Examples 1 to 3 are 288ppm, 250ppm, and 226ppm, respectively. The higher the polycrystalline mullite whisker content, the lower the water content. The water contents of the diaphragms prepared from the lithium battery slurries of Comparative Examples 1 to 7 are 1928ppm, 2500ppm, 2110ppm, 1955ppm, 2360ppm, 2203ppm, and 2550ppm, respectively. The water contents of the diaphragms prepared from the lithium battery slurries of Comparative Examples 1 to 7 are much higher than those of the embodiments;
[0082] The membrane rupture temperature of the diaphragm prepared from the lithium battery slurry of Examples 1 to 3 is greater than that of the comparative example, and the mechanical strength of the diaphragm prepared from the lithium battery slurry of Examples 1 to 3 is better.
[0083] The batteries obtained in the above embodiments and comparative examples were charged and discharged 500 times. The test results are shown in Table 4.
[0084] Table 4
[0085]
[0086] It can be seen from Table 4 that the efficiency (cycle rate) of the batteries prepared in Examples 4 to 6 is greater than that in the comparative example, and the leakage and self-discharge of the batteries are reduced.
[0087] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A low-water content and high-cycle rate lithium battery separator, comprising: The base film and the coating on the base film include: polycrystalline mullite whisker, barium sulfate and binder. The ratio of polycrystalline mullite whisker, barium sulfate and binder is (10-20): (15-45): (3-8) by weight.
2. The lithium battery separator according to claim 1, characterized in that: The low-moisture and high-cycle-rate lithium battery separator also includes: a wetting agent and a dispersant. Calculated by weight, the ratio of barium sulfate, the wetting agent and the dispersant is (15-45): (0.05-1.0): (0.1-0.8).
3. The lithium battery separator according to claim 1, characterized in that The adhesive is a polyacrylate adhesive, and the wetting agent is sodium isopropylnaphthalene sulfonate.
4. The lithium battery separator according to claim 1, characterized in that: The dispersant is one or a mixture of sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate and polyvinyl alcohol.
5. The method for preparing a lithium battery separator according to any one of claims 1 to 4, characterized in that: include: The lithium battery slurry is coated on the base film and dried to obtain a coating on the base film, thereby obtaining a lithium battery separator with low moisture content and high cycle rate.
6. A lithium battery slurry comprising: Water, polycrystalline mullite whisker, barium sulfate, binder, wetting agent and dispersant, calculated by mass, the ratio of polycrystalline mullite whisker, barium sulfate, binder, wetting agent and dispersant is (10-20): (15-45): (3-8): (0.05-1.0): (0.1-0.8).
7. The lithium battery slurry according to claim 6, characterized in that Calculated by mass, the ratio of water to polycrystalline mullite whiskers is (55-80):(10-20).
8. Application of barium sulfate and polycrystalline mullite whiskers to synergistically reduce the water content of the diaphragm.
9. Application of barium sulfate and polycrystalline mullite whiskers to synergistically improve the heat resistance of diaphragms.
10. The application of barium sulfate and polycrystalline mullite whiskers to synergistically improve the battery cycle rate.
Citation Information
Patent Citations
Lithium ion battery ceramic diaphragm paste
CN105489819A
In-situ modified barium sulfate whisker, preparation method thereof and lithium ion battery diaphragm
CN112909424A
Diaphragm and battery containing diaphragm
CN114006024A
Preparation method of lithium ion battery diaphragm and lithium ion battery diaphragm
CN118712647A